Partnering to Build Human Resources for Health Capacity in Africa: A Descriptive Review of the Global Health Service Partnership's Innovative Model for Health Professional Education and Training From 2013-2018 - Vanessa B. Kerry; Bonaventure Ahaisibwe; Bridget Malewezi; Deo Ngoma; Patricia Daoust; Eileen Stuart-Shor; Clelia Anna Mannino; Dick Day; Laura Foradori; Sadath A. Sayeed (Kerman University of Medical Sciences, 2022)
Several Sustainable Development Goals (SDGs) (3, 16, 17) point to the need to systematically address massive shortages of human resources for health (HRH), build capacity and leverage partnerships to reduce the burden of global illness. Addressing these complex needs remain challenging, as simple increases in absolute numbers of healthcare providers trained is insufficient; substantial investment into long-term high-quality training programs is needed, as are incentives to retain qualified professionals within local systems of care delivery. We describe a novel HRH initiative, the Global Health Service Partnership (GHSP), involving collaboration between the US government (President's Emergency Plan for AIDS Relief [PEPFAR], Peace Corps), 5 African countries, and a US-based non-profit, Seed Global Health. GHSP was formed to enlist US health professionals to assist in strengthening teaching and training capacity and focused on pre-and in-service medical and nursing education in Malawi, Tanzania, Uganda, Eswatini and Liberia. From 2013-2018, GHSP sent 186 US health professionals to 27 institutions in 5 countries, helping to train 16 280 unique trainees of all levels. Qualitative impacts included cultivating a supportive classroom learning environment, providing a pedagogical bridge to clinical service, and fostering a supportive clinical learning and practice environment through role modeling, mentorship and personalized learning at the bedside. GHSP represented a novel, multilateral, public-private collaboration to help address HRH needs in Africa. It offers a plausible, structured template for engagement and partnership in the field.